Bioethics : an introduction - Talbot, Marianne (Cambridge ; New York : Cambridge University Press, 2012)
"An understanding of the ethical implications of their work is now essential for all scientists. This accessible textbook clearly explains bioethical theories and their philosophical foundations to science students, enabling them to confidently take part in the key ethical debates of biotechnology. Over 200 activities introduce topics for personal reflection and discussion points encourage students to think for themselves and build their own arguments. Highlighting the potential pitfalls for those new to bioethics, each chapter features boxes providing factual information and outlining the philosophical background. Accompanying online podcasts by the author (two of whose podcasts on iTunesU have attracted over 3 million downloads) explain points that might be difficult for beginners. Detailed case studies provide an insight into real-life examples of bioethical problems. Within-chapter essay questions and quizzes, along with end-of-chapter review questions, allow students to check their understanding and encourage broader thinking about the topics discussed"--
Machine generated contents note: Preface; Using this book; Notes for instructors; Part I. Bioethics and Ethics: 1. Biotechnology and bioethics: what it's all about; 2. Ethics in general: ethics, action and freedom; 3. Ethics in the context of society: ethics, society and the law; 4. Ethical theories: virtue, duty and happiness; 5. Identifying and evaluating arguments: logic and morality; 6. General arguments: unnatural, disgusting, risky, only opinion; Part II. The Beginning and End of Life: Section 1. Cloning: 7. Therapeutic cloning: the moral status of embryos; 8. Reproductive cloning: science and science fiction; Section 2. Reproduction: 9. Reproductive freedom: rights, responsibilities and choice; 10. The resources of reproduction: eggs, sperm and wombs for sale; 11. Screening and embryo selection: eliminating disorders or people?; Section 3. Ageing and Death: 12. Ageing and immortality: the search for longevity; 13. Death and killing: the quality and value of life; Part III. In The Midst of Life: Section 4. Our Duties to Ourselves: 14. Human enhancement: the more the better?; 15. Bio-information: databases, privacy and the fight against crime; 16. Security and defence: security sensitivity, publication and warfare; Section 5. Our Duties to Each Other: 17. Food and energy security: GM food, biofuel and the media; 18. Bio-ownership: who owns the stuff of life?; 19. Human justice: the developed and developing worlds; Section 6. Our Duties to Nature: 20. Non-human animals: consciousness, rationality and animal rights; 21. The living and non-living environment: spaceship Earth; Index.
Includes bibliographical references and index.
Keywords: Medical ethics; Bioethics; MEDICAL / Ethics